Hormonal Fluctuation and Ankle Instability in Women – Is There a Correlation? - Vanessa Boggiano; Hayden Hartman BS; Shannon Fehr DO; Arianna Gianakos DO (Foot & Ankle Orthopaedics)
Category: Ankle; Basic Sciences/Biologics Introduction/Purpose: Lateral ankle sprains are one of the most common injuries to occur in the lower extremity, especially amongst female athletes. With higher incidences of ankle sprains and chronic ankle instability in women, it has been postulated that hormonal modulation and ligamentous laxity influences injury propensity. The role of estrogen in muscle mass and laxity has been demonstrated as collagen synthesis is inhibited by estrogen, resulting in increased elasticity and decreased muscle tone and synthesis. During ovulation and luteal phases, when estrogen is highest, greatest laxity is observed. The purpose of this study is to investigate the impact of hormonal fluctuation on ankle stability and ligamentous laxity and whether these variations can contribute to injury propensity. Methods: In November 2023, a systematic review of the MEDLINE, ProQuest, and Cochrane Library databases was performed between 2000 and 2023 based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The following search terms were used: “(sex or gender) AND (ankle stability)” and “(hormone) AND (ankle)”. Articles were included if they evaluated outcomes related to the impact of hormones on ankle stability in healthy patients, included menstrual tracking, were peer-reviewed, had a minimum of 5 patients per cohort, were written in English, were human patients, and were published after the year 2000. Studies with a male control group were included and evaluated, though this was not a requirement for inclusion. Articles were excluded if they evaluated patients that were injured or experiencing other associated pathological processes impacting ankle function or stability. Results: Fourteen articles were included, composed of 2 clinical trials, 5 cohort studies, 5 case series, and 2 cross-sectional studies. There were 253 (76.4%) females at a weighted mean age for females was 21.9 ± 2.0 years (range, 20.0-25.9). Five studies evaluated postural sway and balance properties noting greater sway rates during ovulation when compared with the follicular phase. Greater muscle tone (p < 0.001) and elasticity (p < 0.05) was observed in the follicular phase compared with ovulation for the tibialis anterior, peroneus longus, and lateral gastrocnemius. Significantly higher ankle joint laxity was observed in ovulation (p=0.016) compared to follicular and luteal phases. Conclusion: The findings in this study demonstrate that postural stability, balance, ligamentous laxity, and tendon properties fluctuate throughout the menstrual cycle. The ovulation phase, a state when estrogen levels peak, demonstrated impaired balance with higher postural sway rates, significantly greater ankle joint laxity, and decreased muscle and ligamentous tone and stiffness – an indicator of laxity. These results demonstrate an underlying etiology for the increased propensity to ankle instability in the female athlete. Additionally, syncing an athlete’s workout type and intensity around menstrual cycle phase may be an advantageous strategy for injury prevention.